Partial Differential Equations 1 Foundations and Integral Representations - Sauvigny, Friedrich (New Delhi : Springer India Pvt. Ltd., 2012)
Annotation This two-volume textbook provides comprehensive coverage of partial differential equations, spanning elliptic, parabolic, and hyperbolic types in two and several variables.In this first volume, special emphasis is placed on geometric and complex variable methods involving integral representations. The following topics are treated: integration and differentiation on manifolds foundations of functional analysis Brouwer's mapping degree generalized analytic functions potential theory and spherical harmonics linear partial differential equationsThis new second edition of this volume has been thoroughly revised and a new section on the boundary behavior of Cauchys integral has been added.The second volume will present functional analytic methods and applications to problems in differential geometry.This textbook will be of particular use to graduate and postgraduate students interested in this field and will be of interest to advanced undergraduate students. It may also be used for independent study.
Scholarly & Professional